Congenital distal esophageal obstruction caused by intraluminal mucosal web - Uğuralp, Sema; Ceran, Canan; Demircan, Mehmet (The Turkish Journal of Pediatrics, 2012)
Here, we report a case with intraluminal membrane (web) located in the lower esophagus causing complete obstruction. Esophagogram revealed complete obstruction near the esophagogastric junction. Surgical excision of the esophageal membrane was performed. To our knowledge, only a few cases with membranous esophageal atresia have been reported. It must be remembered in neonates who cannot tolerate feeding.